Циклічність розвитку банківської системи України та її вплив на будівельний комплекс - Скрипченко, І. О. (Ways to Improve Construction Efficiency, 2014)
The article is devoted to the cyclic character of the Ukrainian banking system, which is a requirement for achieving sustainable development of the construction industry and the entire economic system of Ukraine.